Application of a Seven-Target Pyrosequencing Assay To Improve the Detection of Neuraminidase Inhibitor-Resistant Influenza A(H3N2) Viruses - Tamura, Daisuke (Antimicrob Agents Chemother, 2015)
National U.S. influenza antiviral surveillance incorporates data generated by neuraminidase (NA) inhibition (NI) testing of isolates supplemented with NA sequence analysis and pyrosequencing analysis of clinical specimens. A lack of established correlates for clinically relevant resistance to NA inhibitors (NAIs) hinders interpretation of NI assay data. Nonetheless, A(H3N2) viruses are commonly monitored for moderately or highly reduced inhibition in the NI assay and/or for the presence of NA markers E119V, R292K, and N294S. In 2012 to 2013, three drug-resistant A(H3N2) viruses were detected by NI assay among isolates (n = 1,424); all showed highly reduced inhibition by oseltamivir and had E119V. In addition, one R292K variant was detected among clinical samples (n = 1,024) by a 3-target pyrosequencing assay. Overall, the frequency of NAI resistance was low (0.16% [4 of 2,448]). To screen for additional NA markers previously identified in viruses from NAI-treated patients, the pyrosequencing assay was modified to include Q136K, I222V, and deletions encompassing residues 245 to 248 (del245-248) and residues 247 to 250 (del247-250). The 7-target pyrosequencing assay detected NA variants carrying E119V, Q136, and del245-248 in an isolate from an oseltamivir-treated patient. Next, this assay was applied to clinical specimens collected from hospitalized patients and submitted for NI testing but failed cell culture propagation. Of the 27 clinical specimens tested, 4 (15%) contained NA changes: R292K (n = 2), E119V (n = 1), and del247-250 (n = 1). Recombinant NAs with del247-250 or del245-248 conferred highly reduced inhibition by oseltamivir, reduced inhibition by zanamivir, and normal inhibition by peramivir and laninamivir. Our results demonstrated the benefits of the 7-target pyrosequencing assay in conducting A(H3N2) antiviral surveillance and testing for clinical care.